Mitigasi Terjadinya Kecurangan di Sektor Pemerintahan Melalui Perspektif Fraud Hexagon Theory - Dwi Putra, Muhammad Nanda; Basri, Yesi Mutia; Indrawati, Novita (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
The goal of this research is to investigate just how often public servants commit fraud. This study analyzes the effect of compensation, experience, internal control, organizationali commitment, and leadershipiin mitigating the occurrence of fraud in government. The population in this study is the Riau Province Government's State Civil Apparatus. The sampling method was proportionally stratified randomly using Government Civil Apparatus in three local governments with the highest levels of corruption: Riau Province, Kampar Regency, and Siak Regency. A questionnaire was delivered directly to the participants, and some utilized a Google form to collect data. A total of 198 State Civil Apparatus participated in this study. Multiple linear regression was performed to analyze the data using SPSS software. The findings of the study demonstrate that appropriate compensation, experience, integration, internal control, and a high level of organizational dedication and leadership can all help to reduce the risk of fraud. This research will aid in the prevention of government fraud.